Elicited imitation test as a measure of L2 english learners’ interlanguage representations of relative clauses - Teo, Pauline Hwa Ling (2008)
This study examines the use of the Elicited Imitation Test (EIT) to measure second language learners’ underlying knowledge of restrictive relative clauses which will reflect their interlanguage representation of this property. It also investigates the acquisition of relative clauses by two groups of L2 English learners: L1 Malay and L1 Chinese speakers. This study employed two different testing instruments, i.e. the Elicited Imitation Test and the Grammaticality Judgement Test. The study follows the operational definitions established by Ellis (2004), for two constructs corresponding to implicit and explicit knowledge of the linguistic property being tested. Statistical analyses were carried out on the data obtained from the EIT and GJT. Results showed that learners were generally better at judging and imitating grammatical items in the both tests. Scores obtained were also comparable, indicating there was no significant difference between the mean scores obtained by the L1 Chinese and L1 Malay learners. However, it was discovered that when it came to ungrammatical items, learners were less determinate in their judgement and production. They were less proficient in their ability to imitate or judge and recast the ungrammatical items correctly. The results indicate that the L1 Malay and L1 Chinese learners of L2 English have interlanguage representations that differ from native speakers’ underlying representations of the said property. In addition, a correlation coefficient analysis was also conducted between the grammatical and ungrammatical items in both the EIT and GJT, to determine if a correlation exists. The results from the coefficient analysis showed no correlation between the ungrammatical items in both the tests. However, there was a correlation between the grammatical items in the EIT and GJT. This result suggests that the grammatical items in both the tests measure implicit knowledge. A suggestion is forwarded as to why the ungrammatical items in the tests did not correlate